Changes in pulse pressure variation to assess preload responsiveness in mechanically ventilated patients with spontaneous breathing activity: an observational study. (October 2021) - Hamzaoui, Olfa; Shi, Rui; Carelli, Simone; Sztrymf, Benjamin; Prat, Dominique; Jacobs, Frederic; Monnet, Xavier; Gouëzel, Corentin; Teboul, Jean-Louis
Abstract: Background: Pulse pressure variation (PPV) is not reliable in predicting preload responsiveness in patients receiving mechanical with spontaneous breathing (SB) activity. We hypothesised that an increase in PPV after a tidal volume (VT ) challenge (TVC) or a decrease in PPV during passive leg raising (PLR) can predict preload responsiveness in such cases. Methods: This prospective observational study was performed in two ICUs and included patients receiving mechanical ventilation with SB, for whom the treating physician decided to test preload responsiveness. Transthoracic echocardiography was used to measure the velocity–time integral (VTI) of the left ventricular outflow tract. Patients exhibiting an increase in VTI ≥12% during PLR were defined as PLR+ patients (or preload responders). Then, a TVC was performed by increasing VT by 2 ml kg −1 predicted body weight (PBW) for 1 min. PPV was recorded at each step. Results: Fifty-four patients (Simplified Acute Physiology Score II: 60 (25) ventilated with a VT of 6.5 (0.8) ml kg −1 PBW, were included. Twenty-two patients were PLR+. The absolute decrease in PPV during PLR and the absolute increase in PPV during TVC discriminated between PLR+ and PLR– patients with area under the receiver operating characteristic (AUROC) curve of 0.78 and 0.73, respectively, and cut-off values of –1% and +2%, respectively. Those AUROC curve values were similar but were significantly different from that of baseline PPV (0.61). Conclusion: In patients undergoing mechanical ventilation with SB activity, PPV does not predict preload responsiveness. However, the decrease in PPV during PLR and the increase in PPV during a TVC help discriminate preload responders from non-responders with moderate accuracy. Clinical trial registration: NCT04369027 (ClinicalTrials.gov ).